Suitability maps for different crops in the Mekong River Delta, Vietnam - Vu Manh Quyet; Bui Tan Yen; Pham Thanh Vu; Phan Chi Nguyen (CGIAR Initiative on Asian Mega Deltas, 2024)
These maps delineate the monthly suitability for annual crops (rice, maize, and watermelon) and overall suitability for perennial crops (citrus, coconut, longan, mango, pineapple, and sugarcane) in the Mekong River Delta of Vietnam at a resolution of 250m x 250m. Soil physical and chemical properties, topography (slope), climate (temperature and rainfall), and irrigation water were used for evaluating the suitability of annual crops based on the month of sowing and for evaluating the overall suitability of perennial crops, under current and future scenarios. The maps are products of the CGIAR Initiative on Asian Mega-Deltas (AMD).